Discovery of a small-molecule antiviral targeting the HIV-1 matrix protein - Zentner, Isaac (2012)
Due to the emergence of drug-resistant strains and the cumulative toxicities associated with current therapies, demand remains for new inhibitors of HIV-1 replication. The HIV-1 matrix (MA) protein is an essential viral component with established roles in the assembly of the virus. Using virtual and surface plasmon resonance (SPR)-based screening, we describe the identification of the first small molecule to bind to the HIV-1 MA protein and to possess broad range anti-HIV properties.